The Impact of Elements of the Ancient Iraqi Heritage in the Gallery of the Iraqi Natural History Museum: محمود حسين عبد الرحمن (Al-Academy, 2020)
The research addresses the most important elements of the ancient Iraqi heritage represented by architecture and plastic arts being the direct means that preserved the heritage due to the ease of preserving them and the speed of circulating them and diversity of their topics. Through the features of these elements, the research problem has been defined in the form of questions including: what are the most important elements of the ancient Iraqi heritage? What are the plastic arts? What are the most important topics adopted? What is the concept of palm in the ancient Iraqi heritage? What is the evidence for that?Has it been employed in the Iraqi contemporary art? What is the evidence for that? How to employ it in the arts and their effects in the gallery of the Iraqi natural history? The research objective is to highlight (the impact of the elements of the ancient Iraqi heritage in the gallery of the museum). The impact of the elements of the ancient Iraqi heritage in the gallery appeared in this research through employing the object of the palm that prevailed in most of the artistic scenes in the ancient times and it is part of the heritage that has been employed in the palm tanks inside the hall in the plants pavilion as being an important part of the ancient Iraqi heritage